The Creativity of Islamic Religious Education Teachers in Optimizing Learning Amid Limited Media and Time Allocation - Eka Alzahra; Samarotul Silmi; Nur Azizah (STAI Serdang Lubuk Pakam, 2026)
This study aims to analyze the creativity of Islamic Religious Education teachers in optimizing learning despite limitations in teaching materials and time, strategies for managing classroom time, as well as factors that support and hinder teacher creativity. The study employed a descriptive qualitative approach at SMP Negeri 4 Batang Cenaku, with Islamic Religious Education teachers serving as the primary informants, supported by other teachers and students. Data were collected through observation, interviews, and documentation, then analyzed using an interactive model involving data reduction, data presentation, and drawing conclusions, and tested through triangulation of sources and methods. The results indicate that teachers utilize simple media such as whiteboards, textbooks, and the surrounding environment, and employ discussion, question-and-answer, and hands-on practice methods to ensure effective learning. Time management strategies were implemented through careful planning, prioritization of material, and independent assignments. Supporting factors included teacher motivation, school support, and student enthusiasm, while obstacles included limitations in media, internet access, and learning time.